Marital Quality: A Conceptual Review - Siti Rohmah Nurhayati; Faturochman Faturochman; Avin Fadilla Helmi (Faculty of Psychology Universitas Gadjah Mada, 2019)
The quality of marriage gain the attention of researchers for a long time. Various studies have been done, by placing the marital quality as an independent variable or dependent variable. Although research on marital quality has been done for a long time with a wide range of variables, conceptually, the results are not quite satisfactory. This article aimed to describe literature review on the concept of marital quality. The literature search results define quality of marriage as the level of excellence in marriage based on certain characteristics. These particular characteristics or criteria may vary from region to region. The criteria for the quality of marriage may also differ from one period to another. The dimensions of marital quality vary widely, which can be distinguished into intrapersonal and interpersonal dimensions. Meanwhile, factors affecting the quality of marriage are differentiated into internal factors and factors related to the conjugal relationships.